How Costs Influence Decision Values for Mixed Outcomes - Talmi, Deborah; Pine, Alex (Frontiers in Neuroscience, 2012)
The things that we hold dearest often require a sacrifice, as epitomized in the maxim ‘no pain, no gain’. But how is the subjective value of outcomes established when they consist of mixtures of costs and benefits? We describe theoretical models for the integration of costs and benefits into a single value, drawing on both the economic and the empirical literatures, with the goal of rendering them accessible to the neuroscience community. We propose two key assays that go beyond goodness of fit for deciding between the dominant additive model and four varieties of interactive models. First, how they model decisions between costs when reward is not on offer; and second, whether they predict changes in reward sensitivity when costs are added to outcomes, and in what direction. We provide a selective review of relevant neurobiological work from a computational perspective, focusing on those studies that illuminate the underlying valuation mechanisms. Cognitive neuroscience has great potential to decide which of the theoretical models is actually employed by our brains, but empirical work has yet to fully embrace this challenge. We hope that future research would improve our understanding of how our brain decides whether mixed outcomes are worthwhile.